921. Antibiotic Prescribing for Children in Family Medicine Clinics Within a Practice Research Network. (26th November 2018) - Poole, Nicole; Kronman, Matthew; Gerber, Jeffrey S; Baldwin, Laura-Mae; Zerr, Danielle
Abstract: Background: Family medicine clinics provide care for one-third of US children, yet comprehensive data about antibiotic prescribing in this patient population are lacking. We aimed to characterize antibiotic prescribing for children in family medicine clinics. Methods: A retrospective cohort of patients aged 0–17 years with a visit to a family medicine clinic within the Washington, Wyoming, Alaska, Montana, and Idaho (WWAMI) Region Practice and Research Network (WPRN) from January 1, 2014 to April 30, 2017 was studied. Patients with complex chronic conditions were excluded. We defined narrow-spectrum antibiotics as penicillin, amoxicillin, first-generation cephalosporins, sulfonamides, and nitrofurantoin; and broad-spectrum antibiotics otherwise. On the basis of national guideline recommendations and a previously published hierarchical classification system, we assigned diagnoses to one of the 3 tiers: diagnoses for which antibiotics were (1) almost always indicated (e.g., bacterial pneumonia), (2) may be indicated (e.g., pharyngitis), and (3) generally not indicated (e.g., bronchiolitis/bronchitis). Results: We studied 20, 779 pediatric patients with 97, 228 clinic visits. Oral antibiotics were prescribed in 10, 922 (11%) of all encounters. The median rate of antibiotic prescribing among providers was 14% (interquartile range: 4.9%–18.5%). Of all antibiotics prescribed, 51% were broad-spectrum agents. Acute respiratory tract infections (ARTIs) accounted for 67% of all antibiotics prescribed. Of the antibiotics prescribed for ARTI, 25% were for diagnoses where antibiotics are generally not indicated. First-line guideline-recommended antibiotics were prescribed in 80% of acute otitis media, 80% of sinusitis, 68% of pharyngitis, and 31% of community acquired pneumonia diagnoses. Azithromycin monotherapy was prescribed in 52% of community acquired pneumonia diagnoses. Conclusion: Specific targets for improving antimicrobial prescribing within a family medicine practice research network include prescribing of broad-spectrum antibiotics (particularly azithromycin), prescribing for conditions where antibiotics are not indicated, and first-line guideline-recommended prescribing for pharyngitis and community acquired pneumonia. Disclosures: All authors: No reported disclosures.